PREVENTIVE TELEMEDICINE AS A COMPONENT OF ENSURING THE COMPETITIVENESS OF HEALTHCARE PROVIDERS AT THE MICROLEVEL - Chaliuk, Yuliia (Current Problems of Sustainable Development, 2026)
The article examines the role of preventive telemedicine as a factor in ensuring the competitiveness of healthcare providers at the micro level in the context of digital transformation of healthcare and the growing emphasis on preventive care. The application of bibliographic, comparative, and structural-logical analysis of contemporary international and Ukrainian scientific publications made it possible to trace the impact of preventive telemedicine on healthcare accessibility, continuity of patient monitoring, missed appointment rates, patient convenience, and the efficiency of resource utilization in medical organizations. It has been established that its impact is realized through the restructuring of preventive patient pathways, optimization of contact structures, and improved manageability of healthcare delivery processes. A functional model of a medical organization has been identified in which preventive telemedicine is not an isolated digital service but an integrated element of the preventive care framework, ensuring the formation of competitive advantages through a systemic combination of accessibility, continuity, and organizational efficiency. It has been established that competitive advantage at the micro level is not created by the digital telemedicine channel itself, but by its systematic integration into the preventive framework of a medical organization. Additionally, the findings suggest that the effectiveness of preventive telemedicine depends on organizational readiness, standardized clinical and managerial protocols, interoperable digital infrastructure, and coordinated information systems, while hybrid models combining face-to-face and telemedicine consultations are more effective than fully digital or traditional approaches in ensuring continuity and quality of preventive care; the study also emphasizes outcome-based evaluation and the need for quantitative metrics to assess its contribution to healthcare providers’ competitiveness. The evidence base, including scoping reviews of preventive digital interventions in primary care, confirms the overall effectiveness of telemedicine-based solutions, with a high proportion of studies reporting statistically significant improvements in preventive outcomes. In the context of Ukrainian healthcare, the implementation of preventive telemedicine is additionally shaped by institutional readiness and systemic constraints, while simultaneously contributing to reducing territorial disparities in access to medical services and strengthening the resilience of healthcare delivery at the provider level.
Keywords: telemedicine; social services; healthcare services; efficiency of healthcare digitalization; competitiveness; micro level